Predictors for the academic success of first-year physiotherapy students at a South African university - Sfiso E. Mabizela; Ronel Roos; Hellen Myezwa; Joanne Potterton (AOSIS, 2020)
Background: Numerous factors may influence academic performance and success in undergraduate physiotherapy programmes. Understanding these factors could assist with student selection and design of support structures. Objectives: The objective of our study was to explore the amount of variance explained by the National Benchmark Test (NBT) and the National Senior Certificate (NSC) in passing the first year of study and to explore the association between the NBT performance bands and first-year progression outcome. Method: The sample comprised 2013-2017 student cohorts. Hierarchical regression models were used to explore significant predictors for academic success in the first year of study. The chi-square test was used to assess the association between the NBT performance bands and the categorised progression outcome. Results: The NBT domains explained 22% of the variance, R2 = 0.229, F (3, 212) = 20.97, p = 0.000. The four NSC subjects accounted for 20% of the variance. All seven predicting variables contributed to 43% of the variance in the first year of study, R2 = 0.435, F (7, 208) = 27.29, p = 0.000. Associations between NBT domains and GPA: quantitative literacy (Φ = 0.27; p 0.000); academic literacy (Φ = 0.22; p 0.000); mathematics (Φ = 0.18; p = 0.014). Conclusion: Academic success is associated with academic factors as measured by the NBT and physical sciences matriculation results. Clinical implications: Support programmes in the first year of study are needed to improve student performance and success such as additional tutorials and language enrichment programmes.